Pengaruh Penambahan Garam dengan Konsentrasi yang Berbeda Terhadap Karakteristik Kecap Langkitang (Faunus ater) - Safur, Putri; Maulidya, Rulita; Handayani, Lia (Jurnal TILAPIA, 2025)
Faunus ater (commonly known as langkitang) is a type of gastropod from the phylum Mollusca with promising potential as an alternative raw material for fermented soy sauce production. This potential is supported by its relatively high nutritional content, including protein (9.53%), fat (2.38%), moisture (79.97%), and minerals such as calcium (1.017%), phosphorus (0.012%), and iron (0.005%). This study aimed to evaluate the effect of different salt concentrations on the chemical and microbiological characteristics of langkitang-based soy sauce, focusing on NaCl content, total plate count (TPC), pH, and the presence of lactic acid bacteria (LAB). The production process involved washing, steaming, meat separation, ingredient mixing, fermentation, filtration, and cooking. Three salt concentration treatments (A, B, and C) were applied during fermentation. The results showed NaCl levels of 17.70%, 22.90%, and 21.45% for treatments A, B, and C, respectively—all within the acceptable range based on the Indonesian National Standard (SNI). TPC analysis revealed that samples A and B had total microbial counts of <2500 colonies/gram, while sample C had 7.2 × 10³ colonies/gram. The pH values across all treatments ranged from 6.46 to 6.52. Meanwhile, LAB testing returned negative results for all samples, indicating the absence of lactic acid bacteria.